2012
DOI: 10.1007/s12262-012-0600-y
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Spilt Gallstones During Laparoscopic Cholecystectomy

Abstract: To document the incidence of spilt gallstones during laparoscopic cholecystectomy, the cause and consequences of such spillage. The study included 150 consecutive laparoscopic cholecystectomies performed between October 2007 and November 2008. Data was collected in a prospective manner in accordance to proforma. Follow up were performed at the end of 1 week, 1 month, 6 months and 1 year. The spillage of gall stones during surgery occurred in 19.04 % of the cases. Majority of the spillage occurred due to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
7
0
2
Order By: Relevance
“…Perforation of a gallbladder with gallstones spilt into the peritoneal cavity is a frequent complication, especially when associated with acute cholecystitis and larger gallstones [14, 17, 24]. Z’graggen K et al [17] published a prospective study on 10,174 patients and showed that 1.4% complications were due to spilt gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…Perforation of a gallbladder with gallstones spilt into the peritoneal cavity is a frequent complication, especially when associated with acute cholecystitis and larger gallstones [14, 17, 24]. Z’graggen K et al [17] published a prospective study on 10,174 patients and showed that 1.4% complications were due to spilt gallstones.…”
Section: Discussionmentioning
confidence: 99%
“…Перфорация желчного пузыря с изливанием в брюшную полость желчными камнями является частым осложнением, особенно при остром холецистите, при наличии крупных желчных камней и спаек, а также чаще встречается у мужчин, у пациентов с ожирением и пожилых людей [14]. Утечка конкрементов может происходить во время рассечения желчного пузыря из ложа печени, разрыва с помощью зажимных щипцов или во время извлечения желчного пузыря через один из участков порта [14]. Z'graggen K опубликовал исследование на 10 174 пациентах и показали, что 1,4 % осложнений были вызваны пролитыми желчными камнями [15].…”
Section: результаты исследования и их обсуждениеunclassified
“…Recent data suggest that this can be done by the retrieval of stones and either mopping the gallbladder fossa with surgical gauze or by an interoperative wash to evaluate the spilled content. International data suggest that the complications can range from 2.3% and 7% [ 8 ]. This incidence doubles when stones are not removed [ 9 ].…”
Section: Introductionmentioning
confidence: 99%